Studies in the language of Menander - Goldberg, D; Goldberg, Donna (1997)
﻿ In my investigation of the use of the perfect (part I) and of hyperbaton (part II) I address a cross-section of syntactical questions which reflect elements of the language of drama, of New Comedy, of the end of the classical period, of verse, and of a conversational register in a literary dialogue form at times naturalistic, and at others conventional, rhetorical, or formulaic. 1. I describe the use of the perfect indicative in Menander from various angles including a survey of the perfects found in Menander from verbs which were not previously attested in the perfect (1.7); the notion of innovation is challenged in the face of the accident of attestation and the different genres of the different sources, and I refer to the general problems of studying a dead language. In the following section I describe the typical use of perfects by grammatical categories (2.1), and extra- grammatical categories including discourse mode, sentence-type and non-hypotactic dependence (2.2), and lexical criteria (2.3). In the taxonomy of my description and in my analysis I apply the principle that verbal categories and their morphological manifestations are fluid and complex rather than discrete. For example, in my attempt to understand the use of the temporal value of the perfect I take into account compositional elements such as the use of adverbs (2.1.5); for mood, I try to illustrate the illocutionary wealth of the perfect indicative (2.2.2) and relate this to the relative absence of non-indicative perfect forms (2.1.3) as well as to the frequency of perfects in dialogue mode (2.2.1). The principle of the integration of categories, grammatical and metagrammatical, is seen in the correlation between the low incidence of perfects in subordinate clauses (4) and the exposure of other mechanisms for dependence (2.2.3) which are a particularly salient feature of the dialogue mode: dependence may be logical, or communicational ('stimulus and response' 2.2.3b). Along with (2.2.3), and hypotactic subordination (4), I also consider the transitivity of the perfect (3), not only an exercise in description, but in order to argue that in Menander's time (and genre etc.) perfects are less often transitively used than not; I show that examples with direct objects display weak transitivity (3.2.1, 3.2.4). A relatively weak transitive use supports (although is not synonymous with) the argument that these are not 'resultative' perfects in the sense that they approach aorists. My primary aim is to describe the workings of the perfect and its syntactic environment in Menander, and not to enter into the controversy over the chronology of the resultative perfect. However, evidence points to Menander's retaining a classical use of the perfect quite distinct from the aorist: the perfect is not used as a narrative tense (5), and when it is found in narrative passages it either exits the narrative frame or serves as a border or as a rhetorical or structural 'signpost'. In (5) I also discuss some narrative patterns which are typical of New Comedy, and the consistent use of perfects in direct speech within a past setting. 2. Greek word order is 'free but not arbitrary', to quote Marouzeau. One of the less arbitrary features is the tendency for certain modifiers to be adjacent to their head noun. In part III examine the separation of four modifiers from the substantives they modify: numerals (2). indefinites (3), possessives (4) and the demonstrative OUTOC (5). I move from the inherently most closely cohering (numerals) to the most loosely (demonstratives are often interpreted as being in an appositive or predicative rather than an attributive relation). The enclitic forms, especially of possessives (4.3), are more closely studied since they are also used in later classical Greek as an alternative to the dative forms of the enclitic pronouns in the 'sympathetic' function. In such cases (as with 'loose' demonstratives) the affiliation of the genitive enclitic must be reassessed. As an exercise in description, and in the principle of cumulative evidence, I try to interpret the effect created by the use of hyperbaton in terms of degrees of nuance, emotion, and disruption to the sentence. The nature of the intervening element and the structure of the rest of the sentence are important factors. In Menander's genre certain contexts recur, and certain nuances, tones and attitudes tend to be emphasized.